Characteristic and activity of cellulolytic bacteria isolated from mangrove soil in Northern Coast of Aceh Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Dewiyanti I, Darmawi D, Muchlisin ZA, Helmi TZ, Arisa II, Rahmiati R, Destri E, Fanisha S. 2022. Characteristic and activity of cellulolytic bacteria isolated from mangrove soil in Northern Coast of Aceh Province, Indonesia. Biodiversitas 23: 6587-6599. The cellulolytic bacteria as decomposing cellulose bacteria is related to the soil fertility and productivity of the mangrove ecosystem, and the presence and activity of enzymes produced can evaluate them. The study aims to analyze the cellulolytic bacteria characterization, cellulase enzyme activity, and production and to evaluate the molecular biology of cellulase bacteria isolated from the mangrove soil on the northern coast of Aceh Province, Indonesia. This study was conducted at six locations, and soil samples were collected randomly with three replications. The results showed that the purified bacteria produced 39 isolates that grew in CMC selective media. The common bacteria discovered have an irregular colony shape, undulate colony edge, raised colony elevation, and cream pigmentation. The bacilli cell is the most common shape, while 22 bacteria out of the 39 isolates showed cellulase activity. The cellulolytic index (CI) ranged from 0.31 to 4.82, and the highest CI was BTM533 (4.82), followed by BTM622 (2.09). The quantitative analysis showed that the highest specific cellulase activity of BTM533 and BTM622 were at 36 hours and 42 hours with the value of 0.042 U mg-1 and 0.129 U mg-1. Among the bacteria isolates, two cellulolytic bacteria with high cellulase activity were identified as Bacillus safensis and B. altitudinis using the 16S rRNA gene molecularly.
Keywords: 16S rRNA gene, Aceh Province, Bacillus, cellulolytic bacteria, mangrove soil